The effect of the dopamine agonist, apomorphine, on regional cerebral blood flow in normal volunteers. - Grasby, P; Friston, K; Bench, C; Cowen, P; Frith, C; Liddle, P; Frackowiak, R; Dolan, R (1993)
Apomorphine, a non-selective dopamine agonist, has been used as a pharmacological probe for investigating central dopaminergic neurotransmission in psychiatric illness. In this study repeated measurements of regional cerebral blood flow (rCBF) were made in normal volunteers before, and after, the administration of apomorphine (5 or 10 micrograms/kg), or placebo. The difference in rCBF, before and after drug (apomorphine versus placebo), was used to identify brain areas affected by apomorphine. Compared to placebo, both doses of apomorphine increased blood flow in the anterior cingulate cortex. Apomorphine 10 micrograms/kg also increased prefrontal rCBF (right > left). No decreases in rCBF were noted following either dose of apomorphine. Apomorphine-induced increases of anterior cingulate blood flow might serve as an in vivo index of central dopamine function. Such an approach would complement established neuroendocrine challenge paradigms for investigating central dopamine neurotransmission in psychiatric illness.